THE RELATIONSHIP BETWEEN FINANCIAL RATIOS AND COMPANY PERFORMANCE: AN EMPIRICAL STUDY ON THE COAL SUB-SECTOR OF THE IDX 2020–2023 - Indah Mursalini, Wahyu; Nirwana, Ida; Dewi Fortuna, Agita (LPPM STIE EKA PRASETYA, 2025)
Abstract. This study aims to investigate the correlation between financial ratios and corporate performance, focusing on coal sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the period from 2020 to 2023. Employing a quantitative approach, the study utilizes regression analysis to assess how liquidity and profitability ratios influence financial performance. The findings reveal that the liquidity ratio has a statistically significant impact on financial performance, evidenced by a p-value of 0.000, which is below the 0.05 threshold. Conversely, the profitability ratio does not exhibit a significant influence, as indicated by a p-value of 0.440, which exceeds the 0.05 benchmark. These findings suggest that investors should assess a company's financial health before making business decisions. The liquidity ratio plays a crucial role in determining the financial performance of coal sub-sector companies.